CLEANING OF FLUE GASES IN THERMAL POWER PLANTS - Bricl Martin (Journal of Energy Technology, 2024)
In the scope of this paper, all three processes for desulphurization of flue gases (FGD) are presented. These are a dry procedure, a semi-dry procedure, and a wet calcite procedure for desulphurization of flue gases. Each procedure is described, and the main chemical reactions between acid components in flue gases with reagent and schematic flow chart drawings of each desulphurization procedure are presented. The focus of this paper is to acquaint the reader with the technological possibilities for flue gas desulphurization processes.